Investigating the direct infection of ex vivo bone marrow-derived and peripheral blood-derived haematopoietic stem/progenitor cells by HIV-1 - Durandt, Chrisna (University of Pretoria, 2024)
Dissertation (MSc (Medical Immunology))--University of Pretoria, 2023.